Cattle veterinary services in a changing world. (14th March 2015) - Statham, Jonathan; Green, Martin
Abstract : In the first of a series of feature articles in Veterinary Record discussing the state of different sectors of the veterinary profession in the UK and what the future might hold, Jonathan Statham and Martin Green give their perspective on developments affecting the provision of cattle veterinary services.